Continuity markers as an aid for children in finding the peripheral continuity of world maps. Issue 1 (2nd January 2017) - Hennerdal, Pontus
ABSTRACT: Many map readers, including both children and adults, find it difficult to determine where they would be located along the edge of a world map after crossing that edge. Different types of markers have long been drawn close to the map's edge – for example, in an atlas – to help map readers identify the map upon which they will find themselves if that edge is passed. In this study, a method similar to that used to show the continuity between maps in an atlas has been tested to determine whether continuity markers can also be used to help map readers find a world map's actual peripheral continuity. The study involved children between the ages of 10 and 13 years and showed that continuity markers do help children determine the map's actual peripheral continuity, in combination with a lesson that describes how to find the actual peripheral continuity of a world map. This article, therefore, concludes that continuity markers for world maps can be a useful part of map design that clarifies how the edges of a world map fit together for children who have learned to use this tool.